Preparation of polymer-based nanocomposites by different routes - Oliveira, M. (2013)
Since the eighties, polymeric nanocomposites have been intensely investigated due to the performance improvement achieved when a small amount of nanosized particles are added to a polymer matrix. The remarkable changes on physical and mechanical properties of polymers due to the addition of inorganic solid nanoparticles (typically in form of fibres, flakes, spheres or fine particles) is explained by the huge surface area, which increases the interaction between the nanoparticle and the polymer. Moreover, nanocomposites can be produced using conventional polymer processing techniques, which makes them particularly interesting from the production point of view. Therefore, this chapter will make an overview about different routes to prepare polymer-based nanocomposites by extrusion, mainly synthesis of nanoparticles by sol-gel reactions and dispersion of clays in polymer matrices.